Apuleius in European literature Cupid and Psyche since 1650 - Harrison, Stephen 1960-; May, Regine 1971- (Classical presences, 2024)
This incisive entry in the 'Classical Presences' series explores the afterlife and influence of Apuleius' tale of Cupid and Psyche in European literature and art from 1650 to the present